ALGEBRAIC MULTIGRID PRECONDITIONER FOR ELLIPTIC PROBLEMS WITH MIXED TYPE BOUNDARY CONDITIONS II. MULTIGRID PRECONDITIONER - Grigoryan, A. B. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
The present paper, consisting of two parts, is devoted to constructing algebraic multigrid preconditioners for stiffness matrices arising in finite element approximation of elliptic problems in rectangular domains. The Dirichlet condition is placed on one part of the boundary and third type condition on the rest of the boundary. In the second part, using a sequence of two-grid preconditioners from [1], the multigrid preconditioner with inner Chebyshev iterations is constructed.